Preparation of collagen–chondroitin sulfate–hyaluronic acid hybrid hydrogel scaffolds and cell compatibility in vitro - Zhang, Ling; Li, Kuifeng; Xiao, Wenqian; Zheng, Li; Xiao, Yumei; Fan, Hongsong; Zhang, Xingdong (Carbohydrate polymers, 2011)
Ideal scaffolds for tissue engineering should mimic natural extracellular matrix (ECM) as much as possible. The aim of this study was to develop a biomimetic hydrogel scaffold with good operability and stability by collagen self-assembly. To improve physical and chemical performances, the hydrogels were crosslinked with different concentrations of genipin using gel-crosslinking method. Morphology, crosslinking index, and content of glycosaminoglycans of the hydrogel scaffolds were characterized. The potential of the hydrogels as cartilage tissue engineering scaffolds was evaluated by compression test, swelling measurement, in vitro degradation assay, and biocompatibility study in vitro. Results showed that hydrogel scaffold crosslinked with 0.75mM genipin exhibited balanced optimal properties, and excellent cellular compatibility. Since gelation was temperature sensitive and crosslink occurred under mild conditions, the hydrogel scaffold may be well suited as a carrier for chondrocytes transplantation or as cartilage tissue engineering scaffolds.